2015
DOI: 10.1186/s11671-015-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Break Junctions Based on a Perylene-Diimide Cyano-Functionalized (PDI8-CN2) Derivative

Abstract: In this letter, we report the single-molecule conductance properties of a cyano-functionalized perylene-diimide derivative (PDI8-CN2) investigated with gold nano-electrodes. This molecule is of large interest for the fabrication of high-performance and air-stable n-type organic field-effect transistors. Low-bias experiments performed on mechanically controllable break junctions reveal the presence of two different values of the single-molecule conductance, which differ by about two orders of magnitudes. Up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In our case, the −C≡N peak intensity was reduced, and the theoretical ratio with the imide component was restored when we also considered the weight of the new CN* peak. A previous study of PDI8-CN2 on Au electrical conductance showed similar results: the cyano functional groups drove the chemical interaction at the interface processes [ 52 ]. We concluded that the absence of significant changes in BE for all the core levels suggested a weak molecular interaction with the graphene substrate, with the role of the −C≡N groups being mediation of this interface process.…”
Section: Resultssupporting
confidence: 59%
“…In our case, the −C≡N peak intensity was reduced, and the theoretical ratio with the imide component was restored when we also considered the weight of the new CN* peak. A previous study of PDI8-CN2 on Au electrical conductance showed similar results: the cyano functional groups drove the chemical interaction at the interface processes [ 52 ]. We concluded that the absence of significant changes in BE for all the core levels suggested a weak molecular interaction with the graphene substrate, with the role of the −C≡N groups being mediation of this interface process.…”
Section: Resultssupporting
confidence: 59%
“…In this contribution, we present direct transport measurements of deliberately synthesized perylene tetracarboxylic diimide (PTCDI) derivatives bridged across two electrodes in an electrochemical environment. PTCDI and its derivatives are attractive for molecular electronics as they represent a model redox system. ,, Tao et al determined the conductance of PTCDIs at single-molecule level using scanning tunnelling microscopy (STM) break junction techniques and detected large electrochemical gating effect . The Wandlowski group has investigated electrochemical and charge transport properties of symmetrical and unsymmetrical PTCDI derivatives using spectro-electrochemical and electrochemical STM break junction techniques. , Though the concept of electrochemical (electrolyte) gating effect on the charge transport in molecules was initiated by White, Wrighton, and co-workers, electrolyte gating of single organic molecule was experimentally achieved by Haiss et al and by Tao, and further developed by other groups using STM and/or STM break junction techniques. ,, In an electrochemical electrolyte solution, charge transport can be regulated by external perturbation (electrode potential), so-called electrochemical gating. ,, In an STM break junction configuration, the potentials of STM tip and substrate electrodes, acting as the “source” and the “drain” electrodes, are independently controlled by a bipotentiostat using a reference electrode, i.e., the “gating electrode” (Figure A).…”
Section: Introductionmentioning
confidence: 99%
“…The barrier height Φ eff was consequently estimated from the J-V curves as a function of temperature, displaying a linear decrease, with temperatures from 0.35 eV at T = 290 K to 0.08 eV at T = 77 K, respectively. Finally, by considering that the fundamental aspects of the charge transport at the molecular level can provide useful insights about the electrical response of actual organic devices, in collaboration with the Technical University of Delft, we investigated the conductance properties of single PDI8-CN 2 molecules by means of mechanically controlled break junctions with gold nano-electrodes [108]. In the experimental set-up, a nanometric sized gap is obtained by pulling away from each other two fused fingers of a ductile metallic material.…”
Section: Charge Transport Properties At Nano and Molecular Scale Of Pmentioning
confidence: 99%
“…One-dimensional and two-dimensional conductance histograms extracted for high conductance (c) and low conductance (d), respectively. Reproduced with permission [108]. Copyright Springer, 2015.…”
Section: Charge Transport Properties At Nano and Molecular Scale Of Pmentioning
confidence: 99%